Банковская инфраструктура: теоретический анализ содержания - Копченко, Ю.Е. (Культура народов Причерноморья, 2013)
Современный этап развития банковской системы России характеризуется активизацией процессов формирования банковской инфраструктуры. Развитие этих процессов сталкивается с целым рядом проблем, значительная часть которых лежит в плоскости недостаточной теоретической разработанности подходов к трактовке содержания понятия «банковская инфраструктура». Статья посвящена разработке понятийного аппарата, связанного с исследованием банковской инфраструктуры, и принципов организации взаимодействия банков с институтами банковской инфраструктуры. Сучасний етап розвитку банківської системи Росії характеризується активізацією процесів формування банківської інфраструктури. Розвиток цих процесів стикається з цілою низкою проблем, значна частина яких лежить у площині недостатньою теоретичною розробленістю підходів до трактування змісту поняття «банківська інфраструктура». Стаття присвячена розробці понятійного апарату, пов'язаного з дослідженням банківської інфраструктури, і принципів організації взаємодії банків з інститутами банківської інфраструктури. The current stage of bank development is characterized by the activation of the formation processes of banking infrastructure dictated by the strategic objectives to improve the competitiveness of the Russian banking system. The development of these processes is faced with a number of problems, which arose due to the lack of theoretical approaches to the interpretation of the essence of the term “banking infrastructure”. The terminology confusion because of which up to the present time there is no clear understanding about banking infrastructure, the composition of institutions infrastructure that ensures the activities of banks, and the role in improving the quality of banking that banks have to play. All these prevent the development of scientific recommendations for improving mechanisms of the banking infrastructure functioning. The given article is aimed at making a contribution to the theory and practice of banking. It is dedicated to the development of the conceptual framework associated with the research of formation and development of banking infrastructure and the principles of cooperation between the banks and institutions of banking infrastructure.